Kualitas Pelayanan Kesehatan di Puskesmas Rawat Inap Sumbersari Bantul Kota Metro - Widodo, Tri (Universitas Islam Negeri Raden Intan Lampung, 2020)
Abstract: Discrimination in services often arises because perceptions of rights and obligations between service providers and users have not yet reached a common ground. For example the right for each service user to get fair and friendly treatment from service providers. Instead, it is the service user who must be friendly to the service provider so that his affairs become fast and smooth. Of the various types of public services provided by the government, including health services at the Sumbersari Bantul Inpatient Health Center in Metro Selatan Sub-District Metro City. This research will try to find out complaints made by patients or community users of Inpatient Health Centers related to service problems by nursing staff, facilities and facilities available at the Inpatient Health Centers. The results of the study showed that the services provided by the Inpatient Health Center were already good and in accordance with the wishes of the patients, although there were still a number of complaints that needed to be addressed by the Sumbersari Bantul Inpatient Health Center.Keywords: Public Service, Quality of Service, the Health Service Abstrak: Diskriminasi pelayanan sering kali muncul karena persepsi mengenai hak dan kewajiban antara penyedia dan pengguna layanan belum mencapai titik temu. Misalnya hak bagi setiap pengguna layanan untuk mendapatkan perlakuan yang wajar dan ramah dari penyedia layanan. Sebaliknya, justru pengguna layanan yang harus bersikap ramah terhadap penyedia layanan agar urusannya menjadi cepat dan lancar. Dari berbagai jenis pelayanan publik yang diberikan pemerintah, diantaranya adalah pelayanan kesehatan di Puskesmas Rawat Inap Sumbersari Bantul Kecamatan Metro Selatan Kota Metro.Penelitian ini akan berusaha mengetahui keluhan yang disampaikan pasien atau masyarakat pengguna Puskesmas Rawat Inap terkait dengan masalah pelayanan oleh tenaga keperawatan, sarana dan fasilitas yang ada di Puskesmas Rawat Inap tersebut. Hasil penelitan menunjukan pelayanan yang diberikan oleh Puskesmas Rawat Inap tersebut sudah baik dan sesuai dengan keinginan pasien, meskipun masih ada beberapa keluhan yang perlu menjadi perhatian Puskesmas Rawat Inap Sumbersari Bantul.Kata Kunci: Pelayanan Publik, Kualitas Pelayanan, Pelayanan Kesehatan.